2021
DOI: 10.1038/s41419-021-04329-9
|View full text |Cite
|
Sign up to set email alerts
|

STEAP3 promotes cancer cell proliferation by facilitating nuclear trafficking of EGFR to enhance RAC1-ERK-STAT3 signaling in hepatocellular carcinoma

Abstract: STEAP3 (Six-transmembrane epithelial antigen of the prostate 3, TSAP6, dudulin-2) has been reported to be involved in tumor progression in human malignancies. Nevertheless, how it participates in the progression of human cancers, especially HCC, is still unknown. In the present study, we found that STEAP3 was aberrantly overexpressed in the nuclei of HCC cells. In a large cohort of clinical HCC tissues, high expression level of nuclear STEAP3 was positively associated with tumor differentiation and poor progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
(55 reference statements)
3
23
0
Order By: Relevance
“…As STEAP3 is a metalloreductase responsible for reducing cellular Fe 3+ to Fe 2+ [ 53 ], increased expression of STEAP3 preserved cellular Fe 2+ concentrations to phosphorylate and inactivate GSK3β, thus activating Wnt/β-catenin signaling to favor CRC progression. In fact, the oncogenic roles of STEAP3 have already been found in HCC and glioblastoma [ 40 , 54 ], which could partially strengthen our conclusion that STEAP3-AS1 positively correlated with STEAP3 to promote CRC progression.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As STEAP3 is a metalloreductase responsible for reducing cellular Fe 3+ to Fe 2+ [ 53 ], increased expression of STEAP3 preserved cellular Fe 2+ concentrations to phosphorylate and inactivate GSK3β, thus activating Wnt/β-catenin signaling to favor CRC progression. In fact, the oncogenic roles of STEAP3 have already been found in HCC and glioblastoma [ 40 , 54 ], which could partially strengthen our conclusion that STEAP3-AS1 positively correlated with STEAP3 to promote CRC progression.…”
Section: Discussionsupporting
confidence: 81%
“…STEAP3 is a well-documented metalloreductase involved in reducing Fe 3+ to Fe 2+ , thus playing an essential role in cancer progression [ 38 40 ]. Given the role of Fe 2+ on phosphorylating and inactivating GSK3β [ 41 44 ], we therefore speculated that STEAP3-AS1 activated Wnt/β-catenin signaling might be related to STEAP3-mediated Fe 2+ generation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 activates the ERK signaling pathway in hepatocellular carcinoma and colon cancer to regulate the proliferation, invasion and migration of cancer cells ( 25 , 26 ). Zhao et al ( 27 ) reported that the slit guidance ligand 2/roundabout guidance receptor 1 axis promotes the malignant progression of osteosarcoma cells via activation of the proto-oncogene tyrosine protein kinase Src/ERK/c-Myc/6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, STEAP3 mRNA levels are increased and sustain tumor growth under low-iron settings [52]. Wang et al [53] discovered that STEAP3 was abnormally overexpressed in the nucleus of HCC cells. Nuclear STEAP3 expression boosted stemness phenotype and cell cycle progression via the RAC1-ERK STAT3 and RAC1-JNK-STAT6 signaling pathways, which greatly increased HCC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%